Pengaruh pendekatan pembelajaran matematika realistik, interaksi antarsiswa ditinjau dari motivasi intrinsik terhadap hasil belajar matematika - Fauzi , Lalu Muhammad; Hayati, Nila; Wardi, Zaotul; Yazid, Muh (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2024)
This research aims to see whether there is a direct or indirect influence from students' perceptions of realistic mathematics learning approaches and interactions between students in terms of learning motivation on mathematics learning outcomes. The type of research used in this research is quantitative research. All class VIII students of SMPN 1 Suralaga consisting of 6 classes are the population of this study. The sample in this study was class VIII D which was chosen randomly using a simple random sampling technique using a lottery. The instruments used in collecting data were questionnaires and tests. Data were analyzed using path analysis with the help of the Amos 25.0 program. Research results: 1) the realistic mathematics learning approach has a direct effect on students' learning motivation, this can be seen from the P value of 0.037, which is smaller than the significance level of 0.05; 2) interaction between students has a direct effect on students' learning motivation, this can be seen from the P value of 0.049, which is smaller than the significance level of 0.05; 3) the realistic mathematics learning approach has a direct effect on mathematics learning outcomes, this can be seen from the P value of 0.035, less than the significance level of 0.05; 4) interaction between students has no direct effect on mathematics learning outcomes, this can be seen from the P value of 0.088 which is greater than the significance level of 0.05; and 5) student learning motivation has a direct influence on mathematics learning outcomes, this can be seen from the P value of 0.023, which is smaller than the significance level of 0.05.